Vloga javnih obdarovanj otrok v prvem desetletju praznovanja novoletne jelke v Sloveniji - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2017)
The article describes public present giving to children as part of the novel, socialist New Year's tree celebrations, which the new authorities introduced after the Second World War. It presents the ways of providing the necessary means, present giving to pre-school and school children, and present giving to underprivileged, ill, and special need children. Introducing Father Frost as the bringer of presents, they wanted to replace St Nicholas and Santa Claus, and point out the "new" attitude to children by giving them presents in public. Present giving was part of the social education that was to fill the children with enthusiasm for the new system, to stimulate them to be diligent pupils in the short term, and to contribute to the formation of "good citizens" in the long term. The article describes public present giving to children as part of the novel, socialist New Year's tree celebrations, which the new authorities introduced after the Second World War. It presents the ways of providing the necessary means, present giving to pre-school and school children, and present giving to underprivileged, ill, and special need children. Introducing Father Frost as the bringer of presents, they wanted to replace St Nicholas and Santa Claus, and point out the "new" attitude to children by giving them presents in public. Present giving was part of the social education that was to fill the children with enthusiasm for the new system, to stimulate them to be diligent pupils in the short term, and to contribute to the formation of "good citizens" in the long term.
Keywords: ljudski prazniki; novo leto; Public holidays in Slovenia; novoletna jelka; obdarovanje; socialism; socializem; Slovenia; Slovenija